PENGARUH KESEHATAN DAN KESELAMATAN KERJA (K3), KERJASAMA TIM, DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN - Sari, Prastiwi Nilam; Sumartik, Sumartik; Abadiyah, Rifdah (Universitas Bina Taruna Gorontalo, 2025)
This research aims to determine the influence of Occupational Health and Safety (K3), Teamwork, and Individual Characteristics on employee performance at PT. Bella Agung Citra Mandiri. This research utilized a quantitative approach method with a descriptive design, involving 95 respondents as a sample determined by the population. Collect the required primary data through questionnaires, as well as secondary data from related literature. Data analysis was carried out using SPSS 25, including classic assumption tests, validity, reliability and hypothesis testing. Employee performance is partially influenced by occupational health and safety (K3), teamwork, and individual characteristics. These findings indicate that improving these aspects can contribute to improving performance in the company. The conclusions of this research emphasize the importance of implementing K3 and good teamwork, as well as understanding individual characteristics to achieve optimal organizational goals.